Fabrication and performance evaluation of Integrated Solar Driven Membrane Distillation System with Serpentine-shape of Flat Plate Solar Collector for Seawater Desalination - M. A. H., M. Hanoin; N. S., Mohammed; M. A. I., Z. Arris; A. I., Abu Bakar; Nadzirah, Mohd Mokhtar; Amir, Abdul Razak (Universiti Teknologi Malaysia, 2019)
Solar-powered membrane distillation (SPMD) system has gained its popularity in desalination application for past decade credit to the system efficiency in producing pure water and the utilization of renewable energy. However, most of the past SPMD works used commercial solar thermal collector (STC) as the thermal energy supply to the feed solution and the study only focused on the performance of the system in terms of flux and salt rejection. In this work, a self-made flat plate solar collector (FPSC) with the serpentine-shape pipe was designed and fabricated to study the effect of the STC towards the membrane performance. Before testing, a simulation work of the fluid flow inside the serpentine-shape pipe of the FPSC was analyzed using NX 10.0 computer-aided design simulation. After that, the efficiency of the self-made FPSC system was tested directly to sunlight in order to identify the maximum irradiance and the temperature of the feed solution. Due to the fluctuation of solar irradiance, the experimental setup of the SPMD system was tested using a solar simulator, and the performance was compared with the membrane distillation (MD) system without integration with FPSC system. Based on the simulation data, it can be concluded that the heat losses across the pipe are due to the slower fluid velocity and sudden pressure drop, which attributed to centripetal force and pressure differences. Meanwhile, the outdoor evaluation data showed that the temperatures of collector and water inside the feed tank could reach up to 84°C and 64°C, respectively when the maximum irradiance of 938 W/m2 was applied. For the performance evaluation between with and without the self-made FPSC system, it can be seen that only marginal difference can be observed for the permeate flux and salt rejection with an average difference of 6.06% and 1.29%, respectively.